2014
DOI: 10.1007/s00705-014-2023-5
|View full text |Cite
|
Sign up to set email alerts
|

Complete genome sequence of Tunisvirus, a new member of the proposed family Marseilleviridae

Abstract: Marseillevirus is the founding member of the proposed family Marseilleviridae, which is the second discovered family of giant viruses that infect amoebae. These viruses have been recovered from environmental water samples and, more recently, from humans. Tunisvirus was isolated from fountain water in Tunis, Tunisia, by culturing on Acanthamoeba spp. and is a new marseillevirus. We describe here its 380,011 base-pair genome. A total of 484 proteins were identified, among which 320 and 358 have an ortholog in Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
49
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 36 publications
2
49
0
Order By: Relevance
“…These particles are thus not visible under a light microscope. The Melbournevirus cycle lasts 12 h and is very similar to the previously described replicative cycle of Lausannevirus and Marseillevirus (17)(18)(19)(20)(21)(22). The first stage of the infection corresponded to the internalization of icosahedral particles.…”
Section: Isolation Of Melbournevirussupporting
confidence: 69%
See 3 more Smart Citations
“…These particles are thus not visible under a light microscope. The Melbournevirus cycle lasts 12 h and is very similar to the previously described replicative cycle of Lausannevirus and Marseillevirus (17)(18)(19)(20)(21)(22). The first stage of the infection corresponded to the internalization of icosahedral particles.…”
Section: Isolation Of Melbournevirussupporting
confidence: 69%
“…This then raises the question of how viruses that have been separated long enough to reach locations 15,000 kilometers away and across the Pacific Ocean could have kept their genome sequence more than 98% identical on average. This finding is even more puzzling given that other members of the family Marseilleviridae, such as Tunisvirus and Lausannevirus, exhibit a much lower percentage of nucleotide sequence identity (Ͻ60%) while still being able to infect the same acanthamoeba host with the same apparent efficiency (20,21). Extreme sequence conservation between large DNA viruses isolated from very distant locations has been reported previously but was limited to individual genes (38).…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Comparative genomics showed that these pangenomes are strongly dissimilar. For comparison, 216 and 529 genes were estimated to comprise the core genome and the pangenome of marseilleviruses, which have genomes that are Ϸ20% shorter (46). It is also worth noting that the mean amino acid identity between faustovirus/ASFV orthologous gene pairs is 30%.…”
Section: Isolationanddevelopmentalcycleoffaustoviruswe Documented Thmentioning
confidence: 99%